2001
DOI: 10.1016/s0305-0548(99)00101-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing descent heuristics and metaheuristics for the vehicle routing problem

Abstract: Scope and Purpose. Tabu Search (TS) and Simulated Annealing (SA) have demonstrated to be appropriate metaheuristics for solving NP-hard combinatorial optimization problems, such as the Vehicle Routing Problem with side-constraints. In order to compare the performances of both metaheuristics with each other and with a traditional descent implementation, a comparison of the best solution independent of computing times is fundamentally wrong because metaheuristics have no unambiguous stopping criteria, as opposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…For example, Osman [24] combined TS and SA concepts for the solution search during routing improvement. Van Breedam [25] used three types of routing improvement methods, and then added SA mechanisms for improvements. Tan et al [26] combined TS, SA, and GA to solve the VRP with time window.…”
Section: Approaches For Vrpmentioning
confidence: 99%
“…For example, Osman [24] combined TS and SA concepts for the solution search during routing improvement. Van Breedam [25] used three types of routing improvement methods, and then added SA mechanisms for improvements. Tan et al [26] combined TS, SA, and GA to solve the VRP with time window.…”
Section: Approaches For Vrpmentioning
confidence: 99%
“…In order to narrow the search space and make the process more intelligent, a criterion, called the range delimiter, has been proposed to prevent the selection of too many bad moves (Breedam 2001). The concept of delimiter value is similar to the generation of an initial solution described in the previous Section.…”
Section: Delimiter Valuementioning
confidence: 99%
“…Application of meta-heuristics in location and vehicle-routing is abundant (Golden and Skiscim 1986;Tuzun and Burke 1999;Prins et al 2007;Bräysy et al 2009;Prins et al 2009). It has been reported that Tabu Search and Simulated Annealing are appropriate meta-heuristics for solving NPhard combinatorial optimisation problems (Breedam 2001) of location-routing. However plenty of scope is still there to judge the efficacy of other meta-heuristics in solving locationrouting problems.…”
Section: Literature Reviewmentioning
confidence: 99%